2011
DOI: 10.1590/s0001-37652011000200030
|View full text |Cite
|
Sign up to set email alerts
|

Human mobility on the Brazilian coast: an analysis of strontium isotopes in archaeological human remains from Forte Marechal Luz Sambaqui

Abstract: This study investigated strontium isotopes in the dental enamel of 32 human skeletons from Forte Marechal Luz sambaqui (shellmound), Santa Catarina, Brazil, aiming at identifying local and non-local individuals. The archeological site presents pot sherds in the uppermost archeological layers. Dental enamel was also examined from specimens of terrestrial fauna 87 Sr/ 86 Sr = 0.71046 to 0.71273 and marine fauna 87 Sr/ 86 Sr = 0.70917 . The 87 Sr/ 86 Sr isotope ratio for individuals classified as locals ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
3
7
0
10
Order By: Relevance
“…Interestingly, some individuals at Jab-II have an unusually high intake of C3 terrestrial proteins, denoting some degree of population variability on the coast. Although the lack of significant isotopic differences between sexes and age is consistent with pervasive food sharing among these populations, the intra-population δ 13 C and δ 15 N variability at Jab-II may point to the presence of non-local individuals, as observed in other preceramic coastal populations [18], perhaps assimilated into the group through post-marital residential practices [83]; however isotopic variability may also be associated to food restrictions among members of the community [84].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, some individuals at Jab-II have an unusually high intake of C3 terrestrial proteins, denoting some degree of population variability on the coast. Although the lack of significant isotopic differences between sexes and age is consistent with pervasive food sharing among these populations, the intra-population δ 13 C and δ 15 N variability at Jab-II may point to the presence of non-local individuals, as observed in other preceramic coastal populations [18], perhaps assimilated into the group through post-marital residential practices [83]; however isotopic variability may also be associated to food restrictions among members of the community [84].…”
Section: Discussionmentioning
confidence: 75%
“…While there is some evidence for consumption of new cultigens like maize by Taquara/Itararé groups [7] and increased consumption of terrestrial resources [18], marine fauna continue to be found at high abundance [19]. Similarly, while pottery is often assumed to be associated with the processing of new produced and foraged foods, with parallels in the southern Brazilian Highlands [16], there is no direct evidence of what it was used for.…”
Section: Introductionmentioning
confidence: 99%
“…assim, a estrutura de Braudel segue aqui como pano de fundo; pano de fundo para a ação, que pode ser encontrada na teoria da prática de Bourdieu (1967Bourdieu ( , 1977Bourdieu ( , 1989 Já para a contextualização local e regional dos resultados, foram realizadas comparações com dados provenientes de estudos em diferentes sítios do litoral catarinense (Bastos et al 2011(Bastos et al , 2014(Bastos et al , 2015Colonese et al 2014;De Masi 2001. Vale destacar que a análise multidimensional dos dados só se fez possível devido a essa comparação com outros estudos e, sobretudo, devido à realização de datações individualizadas de diversos sepultamentos do sítio armação do sul.…”
unclassified
“…As análises isotópicas realizadas por Bastos (2009) e Bastos et al (2011) em indivíduos sepultados nos níveis pré-cerâmicos e cerâmicos do sambaqui Forte Marechal Luz (Ilha de São Francisco do Sul, SC) indicaram predomínio de indivíduos autóctones em ambos os níveis. Do conjunto de 32 indivíduos analisados, unicamente três não eram locais e provêm do interior, dois estavam enterrados no nível cerâmico do sambaqui, e um no nível pré--cerâmico.…”
Section: Os Sítios "Mistos" Ou Sítios Costeiros Com Cerâmicaunclassified